Estratificación de la cartera activa en el mejoramiento del procedimiento de cobro coactivo de tributos en la dirección zonal 3 del servicio de rentas internas del periodo fiscal 2015 - Arias Bautista, Gina Paola (2017)
The present study investigates the stratification of the active portfolio of firm tax obligations in relation to the process of management of coercive collection made by the Dirección Zonal 3 del Servicio de Rentas Internas during fiscal year 2015, in order to establish a differentiated procedure recovery of small amounts of tax debts. This research takes into account the need to clarify the active portfolio of tax credits, since most of the same measure in number of obligations, is composed of low-amount debts, but whose amount is not representative; the operational capacity of the administrative area of Cobro is limited; whereas, the execution of these debts entails a procedure covered by deadlines and formalities that must be fulfilled. To this end, an examination was made of the cost of managing the collection of taxes by the Servicio de Rentas Internas; also, the constitutional principles of reasonableness, economics, effectiveness and efficiency were analyzed; of national and international legislation to determine the feasibility of applying the legal figure of the Uncollectibility due to lack of Fiscal Interest of the low amount obligations. Its application is based on a minimum portfolio management, the lack of a real economic damage to the Public Finance, and the cost benefit of maintaining a portfolio of debts that due to its materiality is costly to recover. At the same time, it seeks to improve the control of this portfolio and focus the efforts of the Tax Administration to a profitable collection.